Self-assembled multilayers of water glucose modified-chitosan and glucose oxidase for detection of glucose in milk samples - Gulotta, Florencia Alejandra (2022)
Background: A crucial aspect of electrochemical enzymatic biosensor development is the immobilization of the enzymes, as it directly influences the sensitivity of the bioelectrode. Among the different methods used to incorporate enzymes on the surface of the transducers, layer-by-layer (LbL) self-assembly based on electrostatic interaction with polyelectrolytes of opposite charge stands out due to its simplicity and reproducibility. Aims: The aim of the work was to develop an electrochemical glucose biosensor by LbL assembly of a new functionalized chitosan polycation and the enzyme glucose oxidase (GOx). Methods: Chitosan was chemically functionalized with glucose by the Maillard reaction. The resulting polycation, named G-Chit, is soluble in the medium compatible with the enzyme. The bioelectrode was obtained by alternating adsorption of G-Chit and GOx onto carbon paste electrodes. By selecting the number of bilayer of G-Chit/GOX, the enzyme concentration, and the pH, the electroanalytical performance of the biosensor was optimized. The electrochemical responses were characterized by cyclic voltammetry and chronoamperometry. Results: Under optimized experimental conditions, the biosensor exhibited a sensitivity of (0.81 ± 0.03) µA mM-1 in a glucose concentration range of (0.18 to 1.75) mM. Discussion: Results indicated that catalytic response increases both with the number of G-Chit/GOx bilayers and the enzyme concentration, obtaining the best responses for 3 bilayers and 2 mg mL-1, respectively, while the optimum working pH value was 7.0. Conclusions: The analytical response of the biosensor was tested in milk samples with negligible matrix effects, suggesting a potential application in other dairy products. Results show that G-Chit appears promising for the immobilization of enzymes.